Economics 2.0 what the best minds in economics can teach you about business and life - Haring, Norbert; Storbeck, Olaf (Palgrave Macmillan, 2009)
Economics 2.0' makes a case for the argument that economics is not a dry science and that economics principles impact much of our day to day life. Completely without formulas and theoretical ballast, the authors present findings of prominent economists and expand the economic knowledge of their readers.